Android Mobile Learning: MIT App Inventor dan Pengembangannya pada Pembelajaran Matematika - Risma, Risma; Farida, Farida; Andriani, Siska (AlphaMath : Journal of Mathematics Education, 2021)
This study aims to develop mobile mathematics learning media using App Inventor 2. Development using App Inventor 2 will make it easy to access learning because this application is android in nature. The development procedure that will be carried out by the author is using 4D. The data collection techniques I use are interviews, questionnaires and tests. The data processing technique I use is the effect size test. The result of this research is a product, namely mobile learning, which refers to the modified research and development design of the 4D development model. From the results of research using mobile learning with App Inventor 2 student learning outcomes have increased more than before. App Inventor 2 is an application that can be accessed anywhere and anytime it really helps students learn to understand the material first before being taught in class. So, it can be concluded that the media developed by the author is feasible and effective to be used as teaching material to help students in the learning process.